Polarized extremes and the confused centre: Campaign targeting of voters with correlation neglect - Levy, G; Moreno De Barreda, I; Razin, R (Now Publishers, 2021)
We model the effect of competing political campaigns on the opinion of voters who exhibit correlation neglect, i.e., fail to understand that different campaigns might be correlated. We show that political campaigners can manipulate voters' beliefs even when voters understand the informativeness of each campaign separately. The optimal coordination of campaigns involves negative correlation of good news and sometimes full positive correlation of bad news. We show that competition in targeted campaigns has the effect of changing the opinions of different groups in different ways; competition increases polarisation among extreme voters but at the same time increases the variance and the quality of moderates' voting decisions.